2016
DOI: 10.4236/ijcm.2016.710071
|View full text |Cite
|
Sign up to set email alerts
|

Fasting for Laboratory Tests Poses a High Risk of Hypoglycemia in Patients with Diabetes: A Pilot Prevalence Study in Clinical Practice

Abstract: Objective: Fasting for lipid profiles is a deeply-rooted tradition that is being revisited. In patients with diabetes, such fasting poses a risk of hypoglycemia, as observed in recent studies and case reports. This iatrogenic, overlooked, form of hypoglycemia has been referred to as Fasting-Evoked En-route Hypoglycemia in Diabetes (FEEHD). The objective of the study is to determine the prevalence of FEEHD in clinical practice. Methods: A two-page survey was administered to adults with diabetes on antidiabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
3
11
1
Order By: Relevance
“…The research protocol was approved by the Institutional Review Board, and all participants gave written informed consent. This study was based on a recently published study, utilizing similar inclusion and exclusion criteria [ 16 ]. Briefly, inclusion criteria included adult patients who were able to understand and answer the survey questions, who had a confirmed diabetes diagnosis, and who were taking insulin and/or oral hypoglycemic agents or noninsulin injectable medications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The research protocol was approved by the Institutional Review Board, and all participants gave written informed consent. This study was based on a recently published study, utilizing similar inclusion and exclusion criteria [ 16 ]. Briefly, inclusion criteria included adult patients who were able to understand and answer the survey questions, who had a confirmed diabetes diagnosis, and who were taking insulin and/or oral hypoglycemic agents or noninsulin injectable medications.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was a simple language 2-page document asking about the duration and type of diabetes, medication use, and any episodes of FEEHD in the preceding 12 months and if any instructions were given to the patient about medication dose adjustment prior to having laboratory tests. The survey was adapted from the questionnaire used in a recent study [ 16 ]. At the end of the survey, a template notification was made to instruct patients to notify their care providers of any hypoglycemic events to implement preventive measures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonfasting lipid panels are more economical and safer for certain groups, such as elderly or diabetic patients. A pilot study 17 found that up to 27.1% of patients with diabetes reported experiencing a fasting-evoked hypoglycemic event en route to testing because of fasting for blood work. These events are vastly underreported and add to patient morbidity that can easily be avoided by adopting nonfasting lipid testing.…”
Section: ■ Other Benefits Of Nonfasting Lipid Testingmentioning
confidence: 99%